Developing Guided Discovery-Based Learning Device for Improving Middle School Students' Mathematics Problem-Solving Ability - Emi Suryani Putri; Dony Permana; Yerizon Yerizon; I Made Arnawa (Jurnal Gantang, 2022)
According to the 2011 PISA Mathematics Survey, Indonesia ranked 72nd out of 78 countries. This is a very worrying position for the development and quality of Indonesian education in the eyes of the world. This study aims to create a learning device based on guided discovery to enhance students' valid, practical, and effective problem-solving skills. The developed instructional devices are presented as lesson plans and worksheets for high school math students. This development study uses the Plomp model in three phases: pre-production, prototyping, and evaluation. The research subjects are 7th-grade students of SMPN 2 Northern Rao. Experts conduct verification in mathematics education, educational technology, and the Indonesian Language. The practicality of the teaching aid is evident in the results of practicality surveys in teaching practice and questions from students and teachers. Efficiency can be seen in student learning outcomes. The Data Analysis Result Guided Discovery Learning Device is effective because it meets valid criteria in terms of content and design, is practical in terms of implementation, simplicity, and turnaround time, and can improve learning outcomes. In essence, this research can provide an overview for enhancing the quality of education. In addition, it can be used as an indicator to improve students' problem-solving skills by making math learning more accessible and efficient.